Molecular characterization and expressional modulation of IRAK1 as downstream signaling adaptor molecule of TLR-signaling pathways in Labeo rohita following PAMPs stimulation and bacterial infections. Issue 96 (January 2020) - Sadangi, Sushmita; Mohanty, Arpita; Paichha, Mahismita; Gouda, Suchismita; Saha, Ashis; Das, Surajit; Samanta, Mrinal
Abstract: Interleukin-1 receptor associated kinase (IRAK1) is one of the crucial signal transduction mediators in TLR/IL-1R signaling pathways in host immune system. To investigate about it in rohu ( Labeo rohita ), one of the economically important freshwater fish species in the Indian subcontinent, we cloned, characterized and analyzed its expression following bacterial infection and pathogens associated molecular patterns (PAMPs) stimulation. The full-length cDNA of rohu IRAK1 (LrIRAK1) consisted of 2765 nucleotide (nt) having an ORF of 2115 nt encoding a polypeptide of 704 amino acids (aa) with a molecular mass of 70.4 kDa. Structurally, LrIRAK1 consisted of twenty-nine helix, twelve strands and forty one coils making one N-terminal death domain (19–94 aa) and a central serine threonine kinase catalytic domain (or kinase domain) (188-489aa). In addition to these two prominent domains, LrIRAK1 also contained highly conserved amino acids viz., lysine 215 and aspartic acid 314 and threonine 185, 361 which were reported to be important for kinase and phosphorylation activity respectively in other animals. Similar to higher vertebrates, LrIRAK1 also consisted of CDK1 (cyclin-dependent kinase1) at 338–352 aa; NEK2 (NIMA-related kinase 2) at 47–61 aa; NEK6 (NIMA-related kinase 6) at 581–595 aa and AMPK (AMP- activated protein kinase) motif at 518–538 aa. Phylogenetically, LrIRAK1 is closely related to cave fish, common carp exhibiting high similarity (~95%) and identity (~90%). In the uninfected fish, the LrIRAK1 expression was highest in liver (~11.5 fold) and lowest in blood. In response to Aeromonas hydrophila, Edwardsiella tarda and Bacillus subtilis infection and various TLR and NLR-ligands stimulation, the expression of LrIRAK1 was markedly enhanced at various time points in almost all the tested tissues. These results together suggest the key role of LrIRAK1 in pattern recognition receptors (PRRs)-mediated host defense against pathogenic insults. Highlights: The full- length cDNA of LrIRAK1 consisted of 2765 bp, with an ORF of  2115 bp  encoding 704 aa  polypeptide. LrIRAK1  protein comprised of  29 helix, 12 strands and 41 coils. Phylogenetically LrIRAK1 was related to cave fish and common carp. In TLR and NLR-ligands stimulation, LrIRAK1 was induced both in-vitro and in-vivo . In A.hydrophila, E. tarda and B. subtilis infection,   LrIRAK1 gene expression was significantly induced  in various organs.